PERSEPSI GENERASI Z TERHADAP KOMUNIKASI DIGITAL DI ERA MODERN: STUDI KASUS PADA MAHASISWA FISIP UNIVERSITAS PRAMITA INDONESIA - Putri, Yessi Mareta Andari; Baharudin, Baharudin; Cahyono, Yoyok; Koho, Intan Rachmina; Tsabitah, Annastasya; Akramulyaningsih, Dinda Farida Rahayu; Ababil, Thoriq Nuril (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine Generation Z perceptions of digital communication in the modern era, particularly among students at the Faculty of Social and Political Sciences (FISIP) at Pramita Indonesia University. This study employed a qualitative approach, employing observation, interviews with four informants, and literature review. The results indicate that WhatsApp and platforms like Zoom and Discord are the primary choices for academic activities, while social media platforms like Instagram and TikTok are used more for non-academic interactions. While digital communication offers convenience and efficiency, it also faces challenges such as internet instability and the spread of misinformation and misunderstandings. These findings are expected to provide important insights for developing more effective digital communication strategies in both academic and social contexts, as well as provide further insight into the impact of communication technology on young people's behavior in various areas of their lives. These findings form the basis for this research. Furthermore, the study could be expanded to include respondents from diverse backgrounds and geographic locations for more representative and comprehensive results.